An assessment of shear bond strength between ceramic repair systems and different ceramic infrastructures. Issue 4 (23rd April 2015) - Kocaağaoğlu, Hasan Hüseyin; Gürbulak, Ayşegül
Summary The purpose of this study was to evaluate of shear bond strengths between two ceramic repair systems and different ceramic infrastructure materials. One hundred cylindrical specimens of ceramic infrastructure were fabricated with non precious metal alloy, zirconia, alumina, galvano, and glass ceramic: 20 non precious metal alloy (NP), 20 zirconia (Z), 20 alumina (A), 20 galvano (G), and 20 glass ceramic (GC). Specimens were divided into 2 subgroups. One half of the specimens were applied by Clearfil™ (CR) repair system and, another half of that were applied by Cimara&Cimara® Zircon (CZ) repair system. Bonded specimens were stored in 37°C distilled water for 24 h and were thermocycled at 5–55°C for 1, 200 cycles with a 30‐sec dwell time and 5‐sec transfer time. Shear bond strengths were determined with a mechanical testing device. And mode of failure was recorded. Mann Whitney‐U and Kruskal Wallis tests were applied to the data at 95% confidence interval level. Infrastructure groups displayed the following values in megapascals: NP = 10.70 ± 1.88; Z = 9.15 ± 0.80; A = 11.65 ± 0.70; GC = 10.95 ± 0.80; and G = 6.88 ± 0.88. The Mann Whitney‐U test results showed no significant difference between the repair systems. The Kruskal Wallis test results demonstrated significant difference between the infrastructures. The lowest bond strength values were observed in G group. In conclusion, average bond strength values were in accordance with previously reported values, therefore it can be suggested that intraoral repair of ceramic restorations can be temporary, but a satisfying alternative for patients. SCANNING 37:300–305, 2015. © 2015 Wiley Periodicals, Inc.